Improvement of Salt Tolerance Using Wild Rice Genes - Quan, Ruidang; Wang, Juan; Hui, Jian; Bai, Haibo; Lyu, Xuelian; Zhu, Yongxing; Zhang, Haiwen; Zhang, Zhijin; Li, Shuhua; Huang, Rongfeng (Frontiers in Plant Science, 2018)
Salt stress causes significant reductions in rice production worldwide; thus, improving salt tolerance is a promising approach to meet the increasing food demand. Wild rice germplasm is considered a valuable genetic resource for improving rice cultivars. However, information regarding the improvement of salt tolerance in cultivated rice using wild rice genes is limited. In this study, we identified a salt-tolerant line Dongxiang/Ningjing 15 (DJ15) under salt-stress field conditions from the population of a salt tolerant Dongxiang wild rice × a cultivated rice variety Ningjing16 (NJ16). Genomic resequencing analysis of NJ16, DJ15 and Dongxiang wild rice revealed that the introgressed genomic fragments were unevenly distributed over the 12 chromosomes (Chr.) and mainly identified on Chr. 6, 7, 10 and 11. Using quantitative trait locus (QTL) mapping, we found 9 QTL for salt tolerance (qST) at the seedling stage located on Chr. 1, 3, 4, 5, 6, 8 and 10. In addition, sequence variant analysis within the QTL regions demonstrated that SKC1/HKT8/HKT1;5 and HAK6 transporters along with numerous transcriptional factors were the candidate genes for the salt tolerant QTL. The DJ15/Koshihikari recombinant inbred lines that contained both qST1.2 and qST6, two QTL with the highest effect for salt tolerance, were more tolerant than the parental lines under salt-stress field conditions. Furthermore, the qST6 near-isogenic lines with IR29 background were more tolerant than IR29, indicating that qST1.2 and qST6 could improve salt tolerance in rice. Overall, our study indicates that wild rice genes could markedly improve the salt tolerance of cultivated rice.